Envelhecimento e doenças neurodegenerativas crônicas na Amazônia brasileira: influência do nível de atividade física no desempenho de idosos portadores de declínio cognitivo leve e doença de Alzheimer em testes neuropsicológicos da bateria CERAD e no TSM- “teste sua memória”. - GOMES, Mylene Negrão (2022)
By 2025 the number of elderly people in the world will double and by 2050 will reach around two billion individuals, with the majority of them in developing countries. Alzheimer's disease (AD) is the fourth disease that most compromises the quality of life in elderly. Previous studies show positive relationship between physical activity and cognitive health, and decreased incidence of Alzheimer's disease in physically active people, suggesting physical activity as part of the therapeutic strategy in the treatment of dementia. This work aims to investigate whether different levels of physical activity in older adults with mild cognitive impairment and Alzheimer's disease influence cognitive performance in neuropsychological tests, as well as to introduce a Brazilian version of the TSM-"test your memory". It is an analytical, prospective, longitudinal case-control study, performed at the Laboratory of Neurodegeneration and Infection, University Hospital João de Barros Barreto, from January 2009 to January 2011. Ninety five individuals 65 years old or older were divided in three groups: Alzheimer's disease (AD, n = 21), mild cognitive impairment (DCL, n = 31) and control (n = 43). Patients with previous stroke, primary depression, head injury, other dementias and other neuropsychiatric disorders, and serious visuo-auditory deficits were excluded. The participants were submitted to an initial assessment, screening with GDS-5and DSM-IV, the International Physical Activity Questionnaire (IPAQ), CERAD neuropsychological test battery and the TSM - Test Your Memory (Brazilian version).Statistical analysis was performed using one-way ANOVA, , defining the p-value<0.05 to detect significant differences. Female individuals of mixed ethnicity, aged 70 to 79 years predominated in all groups. The average MMSE score between the three groups was significantly different (control: 26.6± 2.2; DCL: 25.1 ± 2.6, DA: 17.3 ± 4.9, p <0.05), however, the TSM proved to be a more sensitive test to distinguish DCL patients from AD (control: 42.4± 5; DCL: 35.5 ± 7.7, DA: 25.7 ± 8, p <0.01 ). The three groups had different mean scores. In the CERAD word list, clock test, TNBr and phonological verbal fluency. The performance in TSM was significantly lower in DCL and AD groups than in the control group. And DA group was worse in this test than the DCL group too. Good correlations were found between the TSM and other tests, especially with the MMSE (Pearson’s coefficient r = 0.79, p <0.0001) and clock test (r = 0.76, p <0.0001). Physical activity level, in the control group was higher than in all other groups. When the level of physical activity and performance on cognitive tests were correlated, there were no significant differences in the different groups, except by a better performance in word recall test from CERAD, and word list in DCL group (DCL "active":4.7 ± 1.8; DCL"not active": 3 ± 1.5,p <0.01). Although a modest improvement was found in cognitive tests of active lifestyle patients as compared to sedentary ones the present results are in line with previous reports that encourage an active life to reduce the risks of aging cognitive decline and Alzheimer’s disease. It is reasonable to assume that longitudinal research of larger samples may provide precious information about cost and bennefits ratios for public health policies.